Inhibition and Production of Anger Cost More: Evidence From an ERP Study on the Production and Switch of Voluntary Facial Emotional Expression - Shangguan, Chenyu; Wang, Xia; Li, Xu; Wang, Yali; Lu, Jiamei; Li, Zhizhuan (Frontiers in Psychology, 2019)
Humans need to flexibly produce or switch different facial emotional expressions to meet social communication need. However, little is known about the control of voluntary facial emotional expression. We investigated the production and switch of facial expressions of happiness and anger in a response-priming task of 23 Chinese female university students and recorded electroencephalographic (EEG) signals. Results revealed that the accuracy decreased, and reaction time was longer in switch conditions relative to non-switch conditions. A frontal-central P2 component demonstrated greater positivity in switch condition compared with the non-switch condition. These results showed that “switch costs effect” occurred in process of the motor control over voluntary facial emotional expressions. Comparing the two facial emotional expressions, the production of angry expressions required longer reaction time. Data from the Contingent Negative Variation (CNV) component revealed that happiness and anger did not differ in the motor preparation phase. While data from N2 and P3 showed that switching from anger to happiness elicited larger N2 amplitudes than the reverse and switching from happiness to anger elicited larger P3 than the reverse. The results revealed that in the switch process phase, the inhibition (N2) and reprogramming (P3) of anger revealed more costs than that of happiness. The findings indicated that both the inhibition and the reprogramming of anger costs more than that of happiness. This study provides a perspective for the study of voluntary facial emotion expression.